Green innovative work behaviour model on generation z employees in the manufacturing industry: An empirical evidence from Indonesia - Winda Widyanty; Dian Primanita Oktasari; Setyo Riyanto; Dewi Nusraningrum; Sih Damayanti; Sik Sumaedi; I Gede Mahatma Yuda Bakti; Anggini Dinaseviani; Prita Prasetya; Mochammad Fahlevi; Aris Yaman (Sustainable Futures)
With increasing global attention to environmental issues, companies are required to improve all aspects of their operations to become more environmentally friendly. This is essential to minimizing the negative impact on the environment, particularly in the manufacturing industry. The green innovative work behaviour of employees plays a key role in enhancing sustainability. To ensure the success of sustainable development practices, companies must actively encourage and support employees' green innovative work behaviour. This study aims to analyze the factors influencing green innovative work behaviour among employees in Indonesia's manufacturing industry, with a specific focus on Generation Z employees. This generation is widely known for its unique characteristics, which differ from those of previous generations. Additionally, they are expected to become the largest workforce in the manufacturing industry within the next few years. Data for this study was collected through a survey using a questionnaire. The sample consisted of 200 Generation Z employees working in the manufacturing industry. The results of this study indicate that green human resource management practices have a significant and positive impact on green innovative behaviour, both directly and indirectly through green empowerment. Other factors were not found to have a significant influence, either directly or indirectly. The theoretical and practical implications of these findings are discussed in this paper.